Success through failure : Luke's paradoxical view of the Christian mission to the Jews - Neagoe, Alexandru (Array, 2018)
The present article sets out to analyze Luke's view of the Christian mission to the Jews. Specific attention is paid to the question of whether in any sense this mission may be considered as being successful or it may be regarded as having a future. A key distinction is introduced between Luke’s representation of the Christian mission to the Jews and his interpretation of it. Thus, the first section looks primarily at how Luke represents the Jewish response to the mission, while the second section explores the way in which he interprets this response. The conclusion of the study is that Luke's concern is neither to show that the mission to the Jews has failed because of a negative response, nor that it has succeeded because of a positive response, but rather that it has achieved its goal and it has a future despite a predominantly negative response.